Organic and hydraulic shock loadings on a Biological Aerated Filter - Mendoza-Espinosa, L. G.; Stephenson, Tom (Selper Ltd., 2001)
The performance of a biological aerated filter (BAF) during short-term (60 min) organic and hydraulic shock loads was investigated. The BAF used for the present experiment was not capable of absorbing high peak organic shock loads when the organic loads were increased from a normal load of 1.2–1.4 kg soluble chemical oxygen demand (sCOD) m-3 d-1 to shock loads between 5.1– 7.3 kg sCOD m-3 d-1, based on empty bed volumes. Nevertheless, the effect on the biomass was limited as normal performance resumed very quickly. Increases in the hydraulic velocity from 0.7–1.0 m h-1 to 1.5–2.9 m h-1 had little effect on BAF performance in terms of soluble COD removal. Yet, sCOD effluent concentrations of <55 mg l-1 (~22 mg l-1 biochemical oxygen demand) were always achieved. The recovery of the reactor in both cases was fast, resuming normal performance within 60 min after the application of the shock load.
Keywords: Biological aerated filter; organic shock loads; hydraulic shock loads